Facts and their interpretation in paleoanthropological enquiries - Tomczyk, Jacek (Studia Ecologiae et Bioethicae, 2016)
The search for truth in the sciences which deal with the prehistoric past seems exceptionally attractive. What is involved in them is not only the historical dimension, but also an attempt at understanding the present moment. This trivial statement may in practice cause a lot of trouble, since the issue at stake is actually not how “truth” is defined, but rather how we arrive at it. We need to remember that while the first stage of the scientific inquiry usually involves the gathering and description of facts, the second stage is mainly concerned with their explanation and interpretation. At both stages of scientific cognition – that is both in the process of obtaining facts and interpreting them – truth can be falsified by mistake or on purpose. Thus, the main aim of science – to make our comprehension agree with the subject (the state of affairs) under scrutiny – can be suppressed by subjective motivation. It is therefore recommendable to present various reasons behind such a peculiar “emendation” of truth in prehistoric research.